The indirect effect of daily flow experience on affective well-being through less negative views on aging - Samuel Finnigan; Jiawan Zhong; Dwight C.K. Tse (Current Research in Behavioral Sciences)
Views on aging fluctuate daily and may be influenced by everyday encounters and routines. By fully immersing and engaging in an activity (i.e., flow experience), adults in middle and late adulthood can enjoy heighted senses of control and competence that help combat their negative views on their age and aging process. This study aimed to examine whether greater daily flow experiences reduced negative views on aging and, in turn, were associated with affective well-being. In a diary study, 83 UK-residing participants aged 50 to 85 (mean = 62.16) completed daily surveys assessing their flow experiences in their main activities, negative views on aging, and positive and negative affect for 14 consecutive days. Multilevel structural equation modeling revealed that at both within- and between-person levels, greater flow experiences were related to lesser negative views on aging and, in turn, greater positive affect and lesser negative affect. Follow-up exploratory analyses indicated that whereas the within-person contemporaneous (i.e., on the same day) indirect effects of flow experiences on positive and negative affect remained significant regardless of chronological age, such effects did not “spill over” to the following days. These findings highlight the need to consider daily engagement in flow-conducive activities and call for a lifespan perspective to better understand its association with daily views on aging.